Сучасні археологічні знахідки на території України - Луніна, К. О. (ХНУРЕ, 2020)
The purpose of this work is to systematize archeological finds of modem period. There were ancient peoples many years ago. They lived, worked, looked for food, had their customs and traditions. And now, when time passed by, we, modem society, want to figure out what was long ago: were that peoples nimble, how did they understand what beauty is, when made jewelries, how did they brought up their children and many other questions. Археологічні дослідження території України є важливим джерелом знань про минуле нашої країни. Метою роботи є проаналізувати сучасні археологічні знахідки для вивчення різних періодів історії України.
Keywords: культурне розмаїття; українознавство